Dispersing nanoparticles in liquids - Peukert, Wolfgang; Müller, F.; Polke, R; Stenger, Frank (European Congress on Comminution, 2002)
Dispersing particles in liquids is a key requirement for a diversity of applications including pigments for coating applications, ceramic materials, fillers in polymers and tailored rheology of suspensions. Dispersing is especially demanding when the primary particle size is in the nanometer size range. In order to overcome the adhesion forces, high stress intensities are required. However, the high mobility of primary particles may lead to fast aggregation, which has to be prevented by adequate stabilisation of produced primary particles. The dispersion apparatuses and their influencing parameters are discussed. A special problem is the evaluation of the degree of defragmentation. The results of different purposes are presented and discussed. Unanswered questions should lead to further investigations including systematic fundamental studies on model systems, to understand the product behaviour better.
UnivIS-Import:2015-04-16:Pub.2002.tech.ITC.mechve.disper
Keywords: dispersing; defragmentation; liquids